If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(2x-8)=-72
We move all terms to the left:
3(2x-8)-(-72)=0
We add all the numbers together, and all the variables
3(2x-8)+72=0
We multiply parentheses
6x-24+72=0
We add all the numbers together, and all the variables
6x+48=0
We move all terms containing x to the left, all other terms to the right
6x=-48
x=-48/6
x=-8
| 11x=5x-48 | | 3r=6/23 | | -5x-1/6+8=2 | | 6u=2u-24 | | 2(2v-9)+1=5v-17+9v | | v-4.16=7.1 | | -4(-5u+9)-4u=4(u-5)-7 | | -15=-6x+3x-9 | | -3=-20x+16 | | 7/4=x/15 | | -18x+14=-7 | | 7x-6=76 | | 10x-4(7-11x)=-190 | | 35+3x=45+2× | | 10/x=30/24 | | 77=5x-18 | | 100-3(2x-6)=10 | | 4(4j-5)=11j+10 | | 3+3/2x+4=4x+-5/2x | | x/12=80/120 | | 3(1-9a)=22a=2(2a-9)-15 | | Y=0.30x+.731 | | (x+7)^(3)=1000 | | 4w^2+5w+10=0 | | 3n=5n-40 | | Y=0.30*x+.731 | | 1/2-1/8q=(q-1)÷4 | | 3n=5n=40 | | -2x+8=+4 | | -27-3x=-6x-(-8x-3) | | 1/4x-13=4 | | 8s—(8+6s)=20 |